(untitled) (Medical Forum Monthly, 2024)
Objective: To compare the Keratometry (K) readings, axial length and posterior chamber (PC) intraocular lens power taken by IOL master and Sonomed in the Pakistani population. Study Design: Comparative / cross-sectional study Place and Duration of Study: This study was conducted at the Department of Ophthalmology Unit 2, Dow University of Health Sciences, Karachi from 1st March 2017 to 31st May 2017. Materials and Methods: Keratometry readings was recorded in two meridians ,horizontal (K1) and vertical (K2) axes, axial length of the eye was measured and posterior chamber intraocular lens (PC IOL) power was recorded by IOL Master and Sonomed in 74 eyes. Results: The mean K1 of the study group with IOL Master and Sonomed were respectively 43.6±1.9mm and 43.5±1.9mm. and the mean K2 were 44.5±2mm and 44.6±2mm respectively . No significant differences were observed in the measurements of K1 ( p value >0.160) and K2 (p value >0.704).The mean axial length with IOL master was 23.2±0.9mm and was significantly lower than corresponding measurement with Sonomed, 23.3±0.9mm (P<0.001). The PC IOL power recorded with IOL Master (21.5±2.2mm) was significantly higher than that with Sonomed (21.1±2.4mm) (P <0.001). Conclusion: The mean axial length measurement was significantly lower when recorded with IOL master and PC IOL power was significantly higher as compared to Sonomed. There was no significant difference in the mean K1 and K2 measurement when recorded with the two methods.